2005
DOI: 10.1111/j.1601-0825.2005.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of characteristics of elderly people with high VSC level

Abstract: We found that elderly subjects with oral malodor tended to be dentulous and had large deposits of tongue coating. However, oral malodor in the OM group subjects did not appear to cause a disadvantage in their social lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
1
14
0
4
Order By: Relevance
“…Regarding halitosis and the presence of tongue biofilm, there was a significant association in the present study, which is corroborated by Aizawa et al 32 and other studies 16,17 for different age groups. Zellmer et al 21 did not include analysis of tongue biofilm in their study on halitosis with institutionalized elderly people, and recognized this as a significant limitation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding halitosis and the presence of tongue biofilm, there was a significant association in the present study, which is corroborated by Aizawa et al 32 and other studies 16,17 for different age groups. Zellmer et al 21 did not include analysis of tongue biofilm in their study on halitosis with institutionalized elderly people, and recognized this as a significant limitation.…”
Section: Discussionsupporting
confidence: 92%
“…Another factor to consider is that selfperception is subjective and has a multidimensional character, and reports by institutionalized elderly people of good and excellent oral conditions is common, despite the precarious situations identified by clinical examination 8 . Finally, a Japanese study 32 that evaluated institutionalized elderly persons regarding the occurrence of halitosis found that the disorder did not influence their quality of life (measured via SF-36). The confinement of the LTCF environment, with restricted interpersonal relations, and the finding of the present study that most cases of halitosis were of mild intensity, may diminish the psychosocial impact of halitosis and reduce the number of complaints about this condition.…”
Section: Discussionmentioning
confidence: 99%
“…96 In order to overcome the practical drawbacks, portable gas chromatographs were developed to measure sulphur-containing compound levels inside the mouth. 45,97 The scientific and practical value of portable gas chromatographs has to be elucidated by future research projects.…”
Section: Gas Chromatographymentioning
confidence: 99%
“…Halitosis is a common condition that affects most of the adult population 1–3 . In the large majority of cases, halitosis originates in the oral cavity as a result of microbial putrefaction 4 .…”
mentioning
confidence: 99%